Structural and dynamical properties of liquid Ag74Ge26 alloy studied by experiments and ab initio molecular dynamics simulation. (15th June 2015) - Xiong, L.H.; Chen, K.; Ke, F.S.; Lou, H.B.; Yue, G.Q.; Shen, B.; Dong, F.; Wang, S.Y.; Chen, L.Y.; Wang, C.Z.; Ho, K.M.; Wang, X.D.; et al.
Abstract: The structures and dynamics of liquid Ag74 Ge26 alloy at different temperatures were investigated by high-energy X-ray diffraction and ab initio molecular dynamics simulation. The calculated structure factors agree well with the experimental data. Local atomic structure orders have been characterized by angular distribution functions, Honeycutt-Andersen index, Voronoi tessellation and the atomic cluster alignment. We reveal that (i) 〈0,  3,  6,  4,  0〉, 〈0,  2,  8,  4,  0〉, 〈0,  3,  6,  5,  0〉, and 〈1,  3,  4,  5,  1〉 polyhedral dominate in the undercooled Ag74 Ge26 liquid. (ii) The icosahedral-like short-range order is enhanced as the temperature decreases while 〈0,  3,  6,  4,  0〉, 〈0,  2,  8,  4,  0〉, 〈0,  3,  6,  5,  0〉, and 〈0,  1,  10,  2,  0〉 polyhedral become the major short-range orders at low temperature. (iii) The medium-range order which was formed for amorphous phase at ambient temperature persists in the undercooled liquid. In addition, it is found that the diffusion constant of Ag is lower than that of Ge over the studied temperature range. Our findings elucidate that highly dominated short-range order associated with nearest-neighbors shell could empower the development of medium-range order and the formation of metallic glasses.